PERBANKAN SYARIAH DAN PERANNYA DALAM PEMBIAYAAN SEKTOR PERTANIAN DI ACEH - Parman Parman (SYARIAH: Journal of Islamic Law, 2021)
Agriculture, one of the real and productive sectorsin Indonesia as well as the primary sector of the Acehnese livelihood, plays a major role in improving the economic life of the people. However, despite being strategic,agriculturestill faces a number of problems, one of which is the weakness of capital. Capital is an essential element in increasing the production and standard of living of the people, thus its absence can limit the pace of the agricultural sector. To tackle this issue, sharia banking with multi relevant products has been applied in the agricultural sector, which is expected to be a solution for farmers with limited capital. Yet, in reality, sharia banking has not been optimized in being the financial intermediary with the farmer community, and cannot overcome the problematic issue in terms of access of capital. In other words, financing in agriculture has not received proper attention from sharia banking. The existence and implementation of sharia banking financing in Aceh in the agricultural sector were still relatively limited to onlymurabaha and muzharabah schemes. In addition, the effectiveness and implications of such financing on the productivity of the agricultural sector in Aceh were also not particularly effective, given the amount of financing disbursed by the sharia banks in Aceh and the scopes of the agricultural sector were relatively disproportionate. In this case, sharia banking in agricultural financingwas faced with two general obstacles: first, the internal perspectives of banks and related stakeholders that were empirical, such as natural risks, poor quality of human resources, regulation of the government or related agencies that have not fully accommodated agricultural financing, lack of socialization process about agricultural business prospects in banking, and farmers’low understandingon banking activities; and second, the factors that affected financing including the level of NPF, CAR, ROA, DPK and inflation.